Does Profitability Really Matter? Unmasking the Mediating Path Between Market Performance and Firm Value - Briegita, Ruth Anindya; Kahar, Abdul; Parwati, Ni Made Suwitri; Pakawaru, Muhammad Ilham (Dinasti Publisher, 2026)
This study analyzes the role of profitability in mediating the effects of stock price, liquidity, and asset growth on firm value in the healthcare subsector of the Indonesia Stock Exchange for the period 2021-2024. The sample was selected using purposive sampling, resulting in 67 annual reports from 17 companies. Data analysis included descriptive statistic, classical assumption test, and path analysis using SPSS 25. The results indicate that stock price has a significant effect on profitability but does not directly affect firm value. Liquidity has a significant effect on both profitability and firm value. Conversely, asset growth does not affect either profitability or firm value. Profitability mediates the effects of stock price and liquidity on firm value but does not mediate the relationship between asset growth and firm value. these findings indicate that profitability acts as an important mediating variable in the relationship between stock price and liquidity. This study is expected to serve as a reference for companies and investors in making more accurate and strategic decisions, particularly in optimizing financial performance to enhance firm value.